Reactive Oxygen Species as Mediators of Gametophyte Development and Double Fertilization in Flowering Plants - Sankaranarayanan, Subramanian; Ju, Yan; Kessler, Sharon A. (Frontiers in Plant Science, 2020)
Reactive oxygen species (ROS) are toxic by-products of aerobic metabolism. In plants, they also function as important signaling molecules that regulate biotic and abiotic stress responses as well as plant growth and development. Recent studies have implicated ROS in various aspects of plant reproduction. In male gametophytes, ROS are associated with germline development as well as the developmentally associated programmed cell death of tapetal cells necessary for microspore development. ROS have a role in regulation of female gametophyte patterning and maintenance of embryo sac polarity. During pollination, ROS play roles in the generation of self-incompatibility response during pollen-pistil interaction, pollen tube growth, pollen tube burst for sperm release and fertilization. In this mini review, we provide an overview of ROS production and signaling in the context of plant reproductive development, from female and male gametophyte development to fertilization.